Decision Support System for Selecting Santri Organization Leaders Using AHP and TOPSIS - Latifa Yulfitra Nesti; Rivaldy Firmansyah; Muchamad Iqbal; Ahmad Arifin (Komunitas Dosen Indonesia, 2025)
The election of the head of the student organization plays a vital role in the leadership regeneration process within Islamic boarding schools (pesantren). However, this process is often conducted manually and subjectively, leading to potential bias, limited transparency, and a lack of standardized documentation. To address this issue, this study aims to develop a web-based Decision Support System (DSS) that integrates the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to facilitate a fair, measurable, and value-aligned selection process. The selection criteria were identified through interviews and observations, covering five main aspects: morality, discipline, leadership, academics, and socialization. AHP was applied to calculate the priority weights of the criteria, while TOPSIS was used to rank five alternative candidates based on their proximity to the ideal leader profile. The results show that morality emerged as the highest-weighted criterion (0.4672), reflecting the pesantren’s emphasis on personal integrity. Candidate Ziyan Kamil achieved the top preference score of 0.754, indicating the closest alignment with the ideal candidate profile. System functionality was validated using black-box testing, confirming successful implementation of all core features. In conclusion, the developed DSS supports a more transparent, objective, and accountable selection process. It contributes not only to digital transformation in Islamic educational institutions but also serves as a replicable model for participatory and value-based governance in other pesantren environments.